Albedo analysis of dust devil-induced slope streaks and tracks on Mars - Heyer, T.; Raack, J.; Iqbal, W.; Hiesinger, H.; Oetting, A. (Icarus (New York, N.Y. 1962), 2024)
Despite frequent observations of slope streaks and dust devil tracks on the same slopes in various regions on Mars, only a few instances in Arabia Terra have documented slope streaks directly triggered by dust devils. Here we present new observations of dust devil-induced slope streaks in Elysium Planitia and Amazonis Planitia. These observations represent a rare opportunity to study the erosional effects of both dust devils and slope streaks on the martian surface. Since dust devil tracks and the triggered streaks are formed basically simultaneously and are therefore subject to similar alteration processes, e.g., settling dust from the atmosphere, the relative albedo of these features can be determined using high-resolution orbital images. Our relative albedo analyses of twelve dust devil-induced slope streaks revealed that slope streaks appear substantially darker than the respective dust devil tracks. These observations might indicate a stronger erosion of fine-grained material by slope streaks compared to dust devils. •New dust devil-induced slope streaks observed in Elysium Planitia and Amazonis Planitia.•Dust devil-induced slope streaks are significantly darker than dust devil tracks.•Slope streaks might have a stronger erosional effect on martian slopes than dust devils.